Control interno en la empresa centro comunal Cristo del Consuelo de la ciudad de Babahoyo - Yepez Espinoza, Karen Denisse (2021)
The present research work is based on the internal control in the company Centro Comunal "Cristo del Consuelo", located in the city of Babahoyo. The objective of this research is to analyze the internal needs and evaluate the strengths of this company in order to carry out a correct internal control. The method used for the development of this research is descriptive, since the research developed is to establish adverse situations and find the origin of all these problems and in this way innovate and adapt to the changes they entail; In turn, this case study is qualitative in nature, in which an interview was conducted with the company administrator, who is the subject of the study. This project is subject to the line of investigation of financial, administrative, tax, audit, control framed with the subline of companies and public and private institutions. Among the main problems encountered and generating many shortcomings in the company is the inadequate provision of accounting reports, insufficient training and supervision of staff, the lack of inventory management, poor business planning and ultimately failure to meet targets.